Cross-cultural measurement invariance evidence of individualism and collectivism: from the idiosyncratic to universal - Soler-Anguiano, Francisco Leonardo; Rivera-Aragón, Sofía; Díaz-Loving, Rolando (Frontiers in Psychology, 2023)
Introduction Culture plays a fundamental role in shaping human behavior, with individualism and collectivism being key cultural dimensions. However, existing scales for measuring these constructs, such as the INDCOL scale, have demonstrated issues when applied in diverse cultural contexts. To address this, we present the translation and adaptation of the Mexican Vertical and Horizontal Individualism and Collectivism Scale (MXINDCOL) into English, aiming to identify both universal and culture-specific elements. Methods Data were collected from 1124 participants (371 from the United States, 753 from Mexico) using the MXINDCOL and INDCOL scales. Propensity score matching was applied to balance demographic differences between the samples. Confirmatory Factor Analysis (CFA) assessed model fit, and cross-cultural measurement invariance was examined. Reliability, convergent and discriminant validity were also assessed. Results The English-translated MXINDCOL scale demonstrated good model fit in both US and Mexican samples, outperforming the INDCOL scale. Reliability values were higher for the MXINDCOL scale compared to INDCOL. Cross-cultural measurement invariance was established, allowing for meaningful comparisons between the two cultures. US participants scored higher on vertical collectivism, while Mexican participants scored higher on horizontal collectivism and horizontal individualism. Discussion The MXINDCOL scale offers a culturally sensitive measurement of individualism and collectivism, addressing issues found in existing scales. It provides a more accurate assessment of cultural orientations and enriches the understanding of cultural dimensions by incorporating idiosyncratic elements. Further research in diverse cultural contexts is recommended to validate and refine the scale, contributing to a more nuanced understanding of cultural variations in individualism and collectivism.